(untitled) - Richardson, Blake (Hoboken, NJ, 2012)
With proper electronic data management, your business can lower costs, improve efficiency, eliminate duplication, and be protected in the event of a lawsuit. Richardson provides an overview of records management solutions and implementation strategies in plain, non-technical English.
Keywords: Business records,Hồ sơ kinh doanh; Management,Quản lý